Can tablet computers enhance learning in further education?. Issue 2 (3rd March 2016) - Butcher, John
Abstract : Interest in the potential benefits of providing tablet computers to students has grown in recent years, both in UK institutions, and across the world. Limited research studies have been reported in higher education (HE), and primary and secondary school settings, tentatively suggesting a range of positive impacts on learners, but little conclusive research has been published on the introduction of tablets in further education (FE). This article presents a case study of a single, mid-size English FE college, which piloted the provision of tablets to bounded groups of students and teachers in four diverse curriculum areas. The author was invited to help design the college's evaluation of the pilot, which would inform a potential business case to extend the pilot to all students. One element was a qualitative research project, with data captured through a series of focus group interviews with all 64 students who received tablets, and separate interviews with their ten teachers. Findings are reported here, exploring the extent to which students and teachers perceived learning benefits from the tablets: for some learners, this was reported as enhancing the organisation of learning; supporting greater independence of learning and enabling more purposive learning. Barriers to learning enhancement were also identified, including institutional issues (frustration with technical infrastructure), and individual learner disengagement (distraction and surface engagement with mere 'novelty'). Concluding that the tablets' clear benefits were not automatically transformative, and engagement was not uniform, findings are relevant to FE managers and leaders of other institutions considering tablets as a possible learning panacea.